Trasplante hepático como tratamiento de rescate en lesiones biliares complejas irreparables - Blanco-Sosa, Roberto Lázaro (2026)
Latrogenic biliary tract injuries are serious complications of hepatobiliary surgery that can progress to liver failure, recurrent cholangitis, and secondary biliary cirrhosis. Liver transplantation is an infrequent rescue option. This review aims to synthesize the evidence on liver transplantation as a rescue treatment for irreparable biliary injuries, analyzing indications, outcomes, and candidate selection criteria. A narrative literature review (2000–2025) was conducted in international databases, prioritizing reviews, clinical series, and guidelines, with emphasis on prognostic factors and indication scenarios. Liver transplantation represents less than 2% of indications, but it is the only curative option for irreversible liver damage or reconstructive failure,with a five-year survival rate of 70–80%.Recurrent cholangitis may indicate transplantation even without end-stage liver failure. The access to transplantation through MELD scoring varies and is limited in Latin America. It should be considered in specialized centers; key factors include patient selection, advanced fibrosis, and recurrent cholangitis.